Exploring Synthetic Routes to Heteroleptic UIII, UIV, and ThIV Bulky Bis(silyl)amide Complexes. Issue 20 (6th April 2018) - Goodwin, Conrad A. P.; Tuna, Floriana; McInnes, Eric J. L.; Mills, David P.
Abstract : The bis(silyl)amide N(SiMe3 )2 (N′′) has supported spectacular actinide (An) chemistry for over 40 years, yet surprisingly there are only a handful of An complexes containing larger bis(silyl)amides, for example [U(N**)3 ] [N** = N(SiMe2 t Bu)2 , 1 ]. Herein we report the structural characterization of the U III complexes [U(N**)2 (µ‐I)]2 (2 ), [U(N † ′)2 (µ‐I)]2 [N † ′ = N(Si i Pr3 )(SiMe3 ), 3 ], [U(N †† )( I )2 (THF)2 ] [N †† = N(Si i Pr3 )2 , 4 ], [U(N †† )2 ( I )] (5 ), and [U(N † ′)2 ( I )(THF)] (6 ), and the An IV complexes [An(N**)N(SiMe2 t Bu)(SiMe t BuCH2 ‐κ 2 ‐ N, C )(µ‐Cl)]2 (7‐An, An = U, Th) and [Th(N**)2 N(SiMe2 t Bu)(SiMe t BuCH2 ‐κ 2 ‐ N, C )] (8 ). Low crystalline yields were obtained in all cases, presumably due to facile cyclometallation. Although this precluded full characterization of U III 4 and6, and An IV 7 and8, for U III complexes2, 3, and5 yields were high enough to perform NMR, EPR, NIR/UV/Vis, and FTIR spectroscopy, elemental analysis, and magnetic measurements. Abstract : Herein we report the synthesis and characterization of heteroleptic U III bulky bis(silyl)amide complexes by salt metathesis methodologies and explore the viability of similar synthetic routes to related U IV and Th IV bis(silyl)amide complexes.